A Change Is Gonna Come: Universality, Stability, and Shocks in Personality Traits in Rural India - Arnaud Natal; Christophe Jalil Nordman (Institute of Labor Economics (IZA), 2025)
Taking the case of rural South India, we explore the universality of the Big Five personality traits and their stability over time. We then investigate the effects of two exogenous shocks on trait stability: the demonetisation of November 2016 and the second COVID-19 lockdown. We use an original longitudinal dataset collected in 2016-2017 and 2020-2021. After correcting the data for acquiescence bias and performing factor analysis, we find that three personality traits emerge: emotional stability, plasticity, and conscientiousness. We find no evidence of temporal stability. Results from the covariate-balancing propensity score weighting model shows that the demonetisation impacts plasticity and conscientiousness, with exposed individuals scoring notably higher. The second COVID-19 lockdown exerts a negative impact on emotional stability.
Keywords: D91; G51; O12; 330; Big Five; plasticity; demonetisation; COVID-19; caste; gender; India